Critical reflections on a visit to an inner-city primary health care clinic in Rio de Janeiro - Louis S. Jenkins; Marcos A. Goldraich (AOSIS, 2017)
Introduction: Brazil and South Africa share many sociodemographic and health features that provide many learning opportunities. Brazil's national health system, the Sistema Único de Saúde (SUS) prioritises primary health care since 1994, the year democracy came to South Africa. Two family physicians from these countries met in Rocinha favela in Rio de Janeiro, a densely populated area where poverty, danger, drugs, tuberculosis and mental illness are the focus of the health system. Maria do Socorro Family Clinic: Central to the SUS are the Family Health Teams, consisting of community health workers, nurses, doctors and allied health workers. This clinic in Rocinha has 11 teams, caring for 2700 people each, all visited monthly, preventing illness and promoting health. Patients with mental illness are cared for in a therapeutic residency, with an onsite psychiatrist, psychologist and social worker. The relationships between the health carers and the clinic and the community are collegial and equal, sharing care. Larger than life photos of patients from the community line the walls. Training: A culture of learning is evident, with 18 family medicine residents, student nurses, a small library and a learning centre at the clinic. Local authorities compensate trainees in family medicine more than traditional specialties. Conclusion: Brazil has made massive progress in providing universal health coverage over the last 20 years. South Africa, with not too dissimilar challenges, is embarking on this road more recently. The lessons learnt at clinic and community level in this inner-city clinic could be very useful for similar settings in South Africa and other countries.